Quality of life and environment: solid wastes and well-being in three schools of the high basin of the Sabana river, Acapulco, Guerrero, Mexico - Cañedo-Villareal, Roberto (2015)
This paper presents the research results regarding the classification of the Municipal Solid Waste (MSW) generated by three schools (elementary, middle and high school) on the upper basin of the Sabana River, Acapulco, Mexico; identifies the standard of living of the families of the students in these schools and quality of life (INCAVI) of a representative group of “Kilómetro 42”.  The  in situ classification of the MSW was done considering the Official Mexican Standards; The quality of life is determined according to the IMAI 10X6 rule and the INCAVI according to the Stiglitz Commission technique of the French Government. The elementary school reported the generation of 620 kg  of MSW per school period, 5,7 Kg per capita,  mainly paper (25%); middle school 1255, 10,5 Kg per capita,, mainly garden waste (13%); while the high school reported 1196 Kg of MSW, 11,5 Kg per capita, mainly rigid plastic (26%). Regarding the standard of living, divided into six strata, 65% of elementary school families are among the first and the second, 30% between the third and fourth, and 5% between fifth and sixth; middle school families, 21%, 68,4% and 10,6%; high school families 64,7%, 35,3% and 0%; considering the three schools : 50%, 44,6% and 5,4%, respectively. Regarding the personal perception of quality of life, 50% of people considered good, 31,3% poor and 18,8% very poor; with INCAVI results: 31,3% good, 62,5% poor and 6,3% very poor. That is a positive perception under conditions of limited life.